2020
DOI: 10.1371/journal.pcbi.1007716
|View full text |Cite
|
Sign up to set email alerts
|

The influence of red blood cell deformability on hematocrit profiles and platelet margination

Abstract: The influence of red blood cell (RBC) deformability in whole blood on platelet margination is investigated using confocal microscopy measurements of flowing human blood and cell resolved blood flow simulations. Fluorescent platelet concentrations at the wall of a glass chamber are measured using confocal microscopy with flowing human blood containing varying healthy-to-stiff RBC fractions. A decrease is observed in the fluorescent platelet signal at the wall due to the increase of stiffened RBCs in flow, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 55 publications
1
20
1
Order By: Relevance
“…However, the magnitude of the changes in RBC deformability reported in the literature (ranging between 10% and 50% [38,65,66] to several folds [67,68]) would not support a model where such biomechanical changes alone are sufficient to cause vessel occlusion since previous studies showed that order of magnitude changes in shear modulus are required to impede RBC transit through narrow passages [46]. By contrast, our findings support a new concept where changes in the mechanical properties of the RBC membrane leading to abnormal haematocrit partitioning at bifurcations (via altered radial distributions of RBCs [69][70][71]) would reintroduce, in adult networks, the differences in WSS driving developmental vascular remodelling. Given the cross-species corroboration of important roles of WSS and RBC dynamics in vascular remodelling through different vertebrate model systems, future work should investigate the relevance of the findings to human physiology and whether the predicted WSS differences are sufficient to trigger pathological vascular remodelling.…”
Section: Discussioncontrasting
confidence: 66%
“…However, the magnitude of the changes in RBC deformability reported in the literature (ranging between 10% and 50% [38,65,66] to several folds [67,68]) would not support a model where such biomechanical changes alone are sufficient to cause vessel occlusion since previous studies showed that order of magnitude changes in shear modulus are required to impede RBC transit through narrow passages [46]. By contrast, our findings support a new concept where changes in the mechanical properties of the RBC membrane leading to abnormal haematocrit partitioning at bifurcations (via altered radial distributions of RBCs [69][70][71]) would reintroduce, in adult networks, the differences in WSS driving developmental vascular remodelling. Given the cross-species corroboration of important roles of WSS and RBC dynamics in vascular remodelling through different vertebrate model systems, future work should investigate the relevance of the findings to human physiology and whether the predicted WSS differences are sufficient to trigger pathological vascular remodelling.…”
Section: Discussioncontrasting
confidence: 66%
“…Our results in Fig 7A (pink curve) show that the role of increased stiffness of RBCs in platelets transport in the MA channel is marginal. This finding is consistent with a prior study showing that the influence of RBC deformability on the collisions between RBCs and platelets was negligible [ 97 ]. We also compute the residence time of the platelets within MAs when the RBCs adhesion and increased RBC stiffness are considered.…”
Section: Resultssupporting
confidence: 93%
“…This damage to the endothelium led to inflammation, which causes endothelial dysfunction in SCD, contributing to crises 33 . Given that stiffened, HBS-rich RBCs have a higher propensity to marginate, i.e., migrate near the blood vessel wall 45 ,we anticipate these altered cells are likely well-positioned to cause endothelial damage regardless of their composition in blood. Thus, understanding the rigidity level of the HbS population can offer insight into crisis risk.…”
Section: Discussionmentioning
confidence: 99%